Spaces of Contention Politics: protests against the economic crisis in Madrid and Barcelona in 2011 - Bran Guzmán, Emanuel (Geopolítica(s). Revista de estudios sobre espacio y poder, 2013)
The analysis of social conflict from the perspective of the Contention Politics means to locate certain causal mechanisms to explain, in part, the actions of social movements. Within this stream there are those who are committed to understanding the role played inside the political contention (e.g., Tilly, Sewell, Marston, or Martin and Miller), which has led them to think of it as an essential and constituent element of the social. Charles Tilly proposes an explicative model in order to better integrate spatial dimensions with mechanisms. This work analyzes the social movement called 15-M, emerged along one of the harshest moments of the economic crisis in Spain (2011) in terms of the dialectic relationship between the squares occupations in Madrid and Barcelona as main form to protest an political contention.
Keywords: crisis; contention politics; occupation of public space; social movements; indignants movement 15-M.